HUBUNGAN TINGKAT PENDIDIKAN MASYARAKAT DENGAN PENATAAN LINGKUNGAN PERMUKIMAN DESA TOULIANG KECAMATAN ERIS KABUPATEN MINAHASA - Renaldy Kabesi; Kalvin Salindeho Andaria; Hilda Vemy Oroh (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2022)
Humans and the environment as a unit. The human ability to adapt to the residential environment is influenced by the level of understanding of the environment which can be determined by educational background. This study aims to determine the extent of the relationship between the level of education and the arrangement of the settlement environment in Touliang Village, Eris District, Minahasa Regency. The method used is quantitative with the independent variable (X) being the level of education and the dependent variable (Y) being the arrangement of the residential environment. Based on the results of the contingency coefficient criteria of 0.37 < C < 0.70 Cmax, it can be concluded that the degree of relationship between variable X (level of education) and variable Y (environmental arrangement) has a moderate correlation and tends to be high. Hypothesis testing can be concluded that for 2 the five indicators are greater than 7.81. The percentage of positive answers is sequentially greater than the educational background of Higher Education, Senior High School, Junior High School, and Elementary School. This means that there is a relationship between the level of education and the arrangement of the residential environment. The higher the level of education, the better the arrangement of the residential environment for the residents of Touilang Village, Eris District, Minahasa Regency.